Serum Levels of C-Reactive Protein and Interleukin-6 in Patients with Acute Streptococcal Tonsillitis: Kadar Protein C-Reaktif dan Interleukin-6 Serum pada Pasien dengan Tonsilitis Streptokokus Akut - AL-Isawi, Safaa A. (Universitas Muhammadiyah Sidoarjo, 2025)
Background; The tonsils get inflamed with acute streptococcal tonsillitis, which is a common bacterial illness mostly caused by Streptococcus pyogenes. Aims of the study: Look at the blood of people who have acute streptococcal tonsils and people who are healthy and not sick to see how much CRP and IL-6 are present. This will help you figure out what kind of illness it is and how bad it is. Methodology: The study looked at the amounts of C-reactive protein (CRP) and interleukin-6 (IL-6) in the blood of 100 people with acute streptococcal tonsils (as shown by positive throat swab cultures) and 50 healthy people of the same age and gender. It ran from January to April 2024. Blood samples were taken in a clean way, centrifuged to get serum, and then kept at -20°C. ELISA kits were used twice to measure the amounts of CRP and IL-6. We didn't include people who had long-term inflammatory diseases or who had recently taken antibiotics. Ethical approval was given for the study, and all subjects gave their informed permission. Result: The study found no significant differences between patients and controls in age, gender, smoking status, or BMI (p > 0.05). Patients showed significantly higher serum levels of CRP (18.6 ± 5.4 mg/L) and IL-6 (42.3 ± 9.8 pg/mL) compared to controls (CRP: 4.1 ± 1.2 mg/L; IL-6: 8.7 ± 2.6 pg/mL) with p < 0.001. A strong positive correlation existed between CRP and IL-6 (r = 0.742, p < 0.001). No significant gender differences were found for CRP or IL-6 levels (p > 0.05). Conclusions: The study concludes that elevated CRP and IL-6 levels in acute streptococcal tonsillitis reflect a strong inflammatory response driven by IL-6–mediated stimulation of CRP production. These biomarkers effectively indicate infection severity and immune activation.Highlight : The study demonstrates significantly elevated CRP and IL-6 levels in patients with acute streptococcal tonsillitis compared to healthy controls, indicating intense inflammation. A strong positive correlation between CRP and IL-6 levels suggests interlinked immune pathways relevant for disease monitoring. No significant gender differences were found in CRP and IL-6 levels, supporting the general applicability of these biomarkers. Keywords : Acute streptococcal tonsillitis, C-reactive protein, Interleukin-6, Inflammation, Biomarkers, Immune response